Regulation of Maturity Based on Marriage Law in Indonesia: A Perspective on Legal Benefits - Novitasari, Ane Fany; Thohir Luth; Djumikasih, Djumikasih; Nur Chanifah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The level of maturity is a reference that a person is capable of carrying out a marriage. Facts in the field show that there are cases of divorce carried out by couples who have met the age requirements. Reaching the minimum age of maturity in marriage is not enough to conclude that a person is mature. In Marriage Law Number 16 of 2019, only the minimum age limit for marriage is explained or it can be explicitly said that a person is an adult it was 19 years old. Meanwhile, you should also consider the emotional maturity of the person. So it is necessary to clarify the oncept of maturity in marriage law in Indonesia. The aim of this research is to examine maturity regulations based on the Marriage Law in Indonesia. This research is normative legal research with a philosophical approach, a statutory approach and a conceptual approach. The techniques used to analyze legal materials are survey, question, read, recite/recal, review using deductive thinking. The results of the analysis show that maturity plays a major role in the success or failure of a relationship, maturity influences a person's ability to truly commit to a lifelong relationship and understand that commitment means giving up all other partner options. Maturity impacts a person's ability to understand concepts and apply the skills necessary to form and maintain healthy relationships. This can be used as a consideration in legal reform in order to create responsive and progressive legal rules.